2011
DOI: 10.1038/ejcn.2011.114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of three consecutive meals on the physicochemical properties of HDL and LDL in individuals with the metabolic syndrome and patients with type 2 diabetes

Abstract: Background/Objectives: Postprandial hyperlipidemia, which is exaggerated and prolonged in insulin-resistant individuals, has been associated with cardiovascular disease. The objective of this study was to investigate whether and how the composition, size and function of high-density lipoprotein (HDL) and low-density lipoprotein (LDL) particles are affected in the postprandial state among males with the metabolic syndrome (MetS) or type 2 diabetes (T2DM), compared with controls. Subjects/Methods: A total of 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Our reported metabolic differences in response to a high-fat challenge between MetS and healthy subjects are in line with what is known from the literature (5,7,(22)(23)(24)(25)(26)(27)(28). Our finding that MetS subjects showed a differential response of the inflammatory markers IL-6, IL-18, 11,12-DiHETrE, and 19,20-DiHoPE to a high-fat challenge as compared to healthy subjects ( Fig.…”
Section: Healthy Subjects Vs Mets Subjectssupporting
confidence: 82%
“…Our reported metabolic differences in response to a high-fat challenge between MetS and healthy subjects are in line with what is known from the literature (5,7,(22)(23)(24)(25)(26)(27)(28). Our finding that MetS subjects showed a differential response of the inflammatory markers IL-6, IL-18, 11,12-DiHETrE, and 19,20-DiHoPE to a high-fat challenge as compared to healthy subjects ( Fig.…”
Section: Healthy Subjects Vs Mets Subjectssupporting
confidence: 82%
“…The OPGLTT induces expected responses in plasma glucose (Ramos-Roman et al 2012 ; Scheffer et al 2011 ), triglyceride (Casas-Agustench et al 2009 ; Esposito et al 2003 ; Krug et al 2012 ; Scheffer et al 2011 ; Zwirska-Korczala et al 2007 ) and amino acid concentrations (Pellis et al 2012 ). Plasma glucose response similar to an OGTT was observed, inducing an insulin response that was prolonged in comparison with the glucose response (Casas-Agustench et al 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic lipoprotein production markers related to cholesterol transport showed inconsistent responses to an OPGLTT. Some studies report increased postprandial total cholesterol and low-density lipoprotein cholesterol (LDLc) levels (Saxena et al 2005 ; Scheffer et al 2011 ), and decreased postprandial HDLc levels (Coutinho et al 2008 ; Scheffer et al 2011 ; Thomsen et al 2003 ), and one study reported increased postprandial HDLc concentrations (Saxena et al 2005 ). Most studies report stable LDLc (Coutinho et al 2008 ; Derosa et al 2010 ; Esposito et al 2003 ; Iraklianou et al 2001 ; Saxena et al 2005 ; Wopereis et al 2013 ), HDLc (Esposito et al 2003 ; Iraklianou et al 2001 ; Wopereis et al 2013 ) and total cholesterol concentrations (Coutinho et al 2008 ; Esposito et al 2003 ; Thomsen et al 2003 ; Wopereis et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated increased oxidisablity of LDL in both hypercholesterolaemic and normocholesterolaemic diabetic patients [58]. Patients with diabetes and metabolic syndrome have both a preponderance of small dense LDL and the increase in the polyunsaturated fatty acids in the particle, hence many important mechanisms that promote the atherogenicity of LDL in hyperglycaemia [59,60].…”
Section: Free Fatty Acidsmentioning
confidence: 99%